The performance of Malaysian universities based on DEA models - Adna, Norfarziah; Mohd Yusoff, Nazhatul Sahima; Rosly, Nor Syafiqah Azwani; Ahmad Marzuki, Nur Syafiqah Izzati; Wan Razali, Wan Nur Amira Balqis (Academica Press Solutions, 2023)
Universities play a vital role in a country’s growth and have the potential to stay in the field of higher education by determining their performance. Thereby, management will not know whether university performance is profitable if it is not measured. Therefore, this project was carried out to determine the efficiency of public universities in Malaysia using Data Envelopment Analysis (DEA) models such as the Charnes, Cooper, and Rhodes model (CCR) and Slack-Based Measure model (SBM). . Public higher education is under tremendous pressure worldwide to improve its performance and quality. This paper examines the efficiency scores of 20 public universities in Malaysia using the CCR and SBM. These 20 public universities state as Decision Making Unit (DMU) and DMU will be efficient if and only if the optimal value of efficiency is equal to 1; otherwise, it is inefficient. Three inputs and five outputs are determined to measure the performance of the university through the graduate student’s marketability. The findings show that out of 20 public universities, 11 public universities are efficient with an efficiency score equal to 1. Meanwhile, the remaining nine public universities showed inefficient score results. Suggestions and improvements are identified to improve the efficiency of those universities in the future. To overcome inefficient universities, the use of the SBM model provides recommendations to consider in measuring efficiencies which are the number of postgraduate students enrolled, number of undergraduate students enrolled, and number of academic staff as the inputs and the number of postgraduates, number of undergraduates, number of graduates working, number of graduates who choose to further studies and number of graduates choose to develop skills as the outputs. All the criteria need to consider for the improvement for the universities to be more efficient.